Suitability for use and their role in achieving customer satisfaction - Wissam Aziz Shenawa Al-Saadi; Riad Hamza Al-Bakri (Journal of Madenat Alelem University College, 2016)
Achieving customer satisfaction is the most important key success factors in the economic units, as it sums up all the competitiveness of priorities on which they depend units in the face of its competitors in the domestic and global markets, due to changes in the business environment and of the intensity of competition, and changes in the tastes of customers and technological development, should be the economic units to go about the application of the concepts that lead to customer satisfaction, when what has been achieved, customer satisfaction, this means that economic units will achieve all its goals. Research gained importance of relying on the application of the concept of fitness for use of the customer’s point of view, through a proposed program helps economic units to access suitability to achieve customer satisfaction and thus be able to increase its market share, and sales growth, and achieve their goals.